Genotoxicity and Trace Elements Contents Analysis in Nile Tilapia (Oreochromis niloticus) Indicated the Levels of Aquatic Contamination at Three Egyptian Areas - El-Sappah, Ahmed H.; Seif, Mohamed M.; Abdel-Kader, Heba H.; Soaud, Salma A.; Elhamid, Mohamed A. Abd; Abdelghaffar, Ahmed M.; El-Sappah, Hamza H.; Sarwar, Huda; Yadav, Vivek; Maitra, Pulak; Zhao, Xianming; Yan, Kuan; et al. (Frontiers in Veterinary Science, 2022)
The toxic waste and pollutants of heavy metals continuously pollute freshwater aquatic reservoirs, which have severe implications on aquatic life and human health. The present work aims to evaluate trace elements (Zn, Mn, Cu, Cd, and Pb) along with three sites, Mariout lake, Abbassa, and River Nile Aswan in Egypt, using Nile tilapia (Oreochromis niloticus) as bioindicator.The quality assurance, health-risk assessment, SDS-PAGE, qPCR and micronucleus test were performed to investigate the effect of different trace elements on Hsp70 gene level and micronuclei formation. We observed the highest expression of Hsp70 protein band of 70 KD and stress-responsive Hsp70 gene in the liver followed by gills of Nile tilapia caught from Mariout and Abbassa, but the lowest expression in Nile tilapia caught from Aswan. Obvious micronuclei were observed under the microscope in erythrocytes, and their number was gradually decreased in the following manners; Mariout>Abbassa>Aswan. Noticeably, Cu, Zn, and Mn contents were low. Still, Pb and Cd contents were higher than the toxicity level recommended by the Food and Agriculture Organization (FAO), The World Health Organization (WHO) and the European Commission (E.C). These results showed that Hsp70's appearance at the two levels of mRNA and protein is an effective indicator for aquatic pollution besides the aberration at the chromosome level represented in the micronucleus test. Furthermore, these results showed that Nile tilapia of Aswan region had comparatively low trace elements contamination and were suitable for consumption.